Comparison of Transurethral Resection of the Prostate (TURP) with 0.5-cm Tissue Preservation Proximal to the Verumontanum and Standard TURP in terms of Postoperative Ejaculation Disorders - Kalyenci, Bedreddin; Yalçınkaya, Fatih Rüştü (Urology Journal, 2025)
Purpose: To compare postoperative ejaculation disorders (EjDs) between transurethral resection of the prostate (TURP) with 0.5-cm tissue preservation proximal to the verumontanum and the standard TURP procedure. Materials and Methods: Between February 2016 and August 2020, 226 patients who underwent TURP for symptomatic benign prostatic hyperplasia were retrospectively screened. The patients were analyzed in two groups: In Group A (n = 106), TURP was performed by preserving 0.5-cm tissue proximal to the verumontanum, while in Group B (n = 120), standard TURP was performed. The postoperative voiding functions and EjD rates were compared. Results: Similar findings were observed in the international prostate symptom score, health-related quality of life score, maximum urine flow rate, and post-void residual volume in both groups. In Group A, ejaculation was preserved in 55 (51.9%) patients, the ejaculation volume was decreased in 13 (12.3%), and EjD developed in 38 (35.8%). In Group B, ejaculation was preserved in 16 (13.8%) patients, the ejaculation volume decreased in 15 (12.5%), and EjD developed in 89 (74.2%). Conclusion: The ejaculatory function of patients can be maintained in the TURP procedure through the preservation of 0.5-cm tissue from the proximal verumontanum. The modification of TURP can further reduce the risks and undesirable effects of the procedure. The implementation of novel surgical technique modifications and technological developments can potentially decrease complication rates. This approach will also eliminate the assumption that the development of EjD is inevitable after prostate surgery.